The Effect of Emotion-focused Couple Therapy Based on Religious Teachings on Social Compatibility and Marital Conflicts - Hamid Shamsipour Shamsipour; Reza Norouzi kouhdasht; Hossein Mohammadi; Elnaz Azari; Mohadeseh Norouzi (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective:Marital conflicts of couples arise due to differences in their needs and satisfying them, self-orientation, irresponsible behavior, and conflict of demands. Social adaptation is adaptive behaviors acquired to meet the surrounding needs that often require the correction of impulses, excitements and attitudes. The main objective of this study was to evaluate the effect of emotion-focused couple therapy based on religious teachings on social compatibility and marital conflicts of couples. Method: The present study was a clinical trial in which a pre- and post-test with control group was used.The statistical population of this study included all couples referring to the family clinic of Shahid Beheshti University in 2016.40 couples were selected by available sampling method and placed in the group of emotion-focused couple therapy based on religious teachings(n=20) and control group (n=20).For the participants in the experimental group, 10 sessions of emotion-focused couple therapy based on religious teachings (90 minutes each session) were held once a week.To collect the data, the Bell's Social Adjustment Scale (BAI) and Marital Conflict Questionnaire (MCQ) were used. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: The findings showed that teaching emotion-focused couple therapy based on religious instructionshas a significant effect on social compatibility of couples (0.34), emotional compatibility (0.59), and job compatibility (0.24, P<0.05). Decrease in cooperation, sex, relationship with the relatives of the spouse; increase in children's protection; loss of effective communication; and separating the finances were 0.37, 0.25, 0.48, 0.15, 0.43 and 0.17, respectively (P<0.05). Conclusion: Religion in the family and the relationship between couples, religious practices, adherence to religious beliefs and values prevent conflicts of individual tendencies and couples, leading to shared patterns of behavior and social compatibility in the family.For downloading the full-text of this article please click here.